2019
DOI: 10.1175/bams-d-19-0110.1
|View full text |Cite
|
Sign up to set email alerts
|

Weather Observations of Remote Polar Areas Using an AWS Onboard a Unique Zero-Emissions Polar Vehicle

Abstract: The Antarctic Plateau is one of the land areas with the largest gaps in surface weather observations on Earth, gaps that are usually filled with simulations provided by climate models. However, these simulated values must be ground-validated, which is particularly difficult and costly in remote polar regions. We designed and developed a Mobile Automatic Weather Station (M-AWS) which, on board a zero-emissions polar vehicle, recorded a large set of ground measurements that could be used to evaluate numerical we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Several YOPP-endorsed projects (for details on YOPP endorsement, see www.polarprediction.net/key-yopp -activities/yopp-endorsement/) contributed to enhanced data collection on various atmospheric and oceanic properties [e.g., Characterization of the Antarctic Atmosphere and Low Clouds (CAALC) at King George Island, Dynamics, Aerosol, Cloud and Precipitation Observations in the Pristine Environment of the Southern Ocean (DACAPO-PESO) in Punta Arenas]. Gonzalez et al (2019) describe a novel approach for providing additional surface observations for the high Antarctic interior during the SOP using a mobile AWS on a wind-powered sled.…”
mentioning
confidence: 99%
“…Several YOPP-endorsed projects (for details on YOPP endorsement, see www.polarprediction.net/key-yopp -activities/yopp-endorsement/) contributed to enhanced data collection on various atmospheric and oceanic properties [e.g., Characterization of the Antarctic Atmosphere and Low Clouds (CAALC) at King George Island, Dynamics, Aerosol, Cloud and Precipitation Observations in the Pristine Environment of the Southern Ocean (DACAPO-PESO) in Punta Arenas]. Gonzalez et al (2019) describe a novel approach for providing additional surface observations for the high Antarctic interior during the SOP using a mobile AWS on a wind-powered sled.…”
mentioning
confidence: 99%
“…13 The zero emission nature of various mobile sensing platforms has also been exploited to obtain a variety of atmospheric measurements. Examples include general weather observations using a wind sled 14 and air quality measurements using bicycles. 15 Analogously, aerial measurements have been obtained by hot air balloons to study atmospheric boundary layer (ABL) winds 16 and cloud properties have been explored via cable cars.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We installed a M-AWS (Mobile Automatic Weather Station) on board a zero-emissions Windsled vehicle (Gonzalez et al, 2019) that followed a 2538 km transect around the African sector of the Plateau in the 2018/19 austral summer, coinciding with the Year of Polar Prediction in the Southern Hemisphere Special Observing Period (YOPP-SH SOP; Bromwich et al, 2020;Jung et al, 2016). The route started on the plateau near Novolazárevskaya station at 3150 m and approached Dome Fuji reaching to 3745 m (Fig.…”
Section: Observationsmentioning
confidence: 99%
“…In this article, we analyse some small-scale temperature structures combining data from meteorological reanalysis and measurements made by different automatic weather stations (AWS), including a mobile automatic weather station (M-AWS) carried on-board a zero emissions polar vehicle (Gonzalez et al, 2019). The mobility of the M-AWS is an advantage in order to study small scale variability and horizontal gradients in a scarcely-observed place like the Antarctic Plateau.…”
Section: Introductionmentioning
confidence: 99%